حماية برامج الحاسب الالكتروني بين براءة الاختراع وحق المؤلف - خلف, محمد موسى (revue mofakir; No 13 (2016): مجلـــة المفكــر, 2018)
This research studies the standpoint of rules and comparative legislations concerning the protection of computer programs as part of the moral rights, branching from the copyrights. The researcher studies protecting these programs according to the copyrights or intellectual property, in accordance with the TRIPS agreement branching from GATT. The researcher discusses through the pages of this research, protecting computer programs according to the patent laws as a harder and longer way with more elaborate procedures and difficulties, but which achieve more thorough protection for the developer or the creator, and how the new trend in western countries started to accept this orientation which prevailed in the mid twentieth century and before when computers were created, but which now puts a condition that the computer program is part of an industrial machine and not a standalone electronic program. By studying comparative laws of program protection, the research discusses the situation in Palestine and resolves that the applied legislation is obsolete and the apparent need for Palestinian legislators to put forward legislations related to copyright in general, which could help investment and protecting the rights of corporations, international institutions, and donors, which is important to a society in a state building phase